2015
DOI: 10.3389/fphar.2015.00279
|View full text |Cite
|
Sign up to set email alerts
|

β1 Integrins as Therapeutic Targets to Disrupt Hallmarks of Cancer

Abstract: Integrins belong to a large family of αβ heterodimeric transmembrane proteins first recognized as adhesion molecules that bind to dedicated elements of the extracellular matrix and also to other surrounding cells. As important sensors of the cell microenvironment, they regulate numerous signaling pathways in response to structural variations of the extracellular matrix. Biochemical and biomechanical cues provided by this matrix and transmitted to cells via integrins are critically modified in tumoral settings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 145 publications
0
86
0
4
Order By: Relevance
“…The interaction of extracellular matrix macromolecules and their cell surface receptors, in particular, integrins, contribute to cell proliferation in physiological and pathological conditions333435. This is realized by the cross-talk between integrins and growth factor receptors, regulatory loop between integrin/FAK and tumor suppressor p53, and integrin-dependent signaling pathways such as PI3K/Akt/mTOR, NF-κB, and MEK/ERK.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of extracellular matrix macromolecules and their cell surface receptors, in particular, integrins, contribute to cell proliferation in physiological and pathological conditions333435. This is realized by the cross-talk between integrins and growth factor receptors, regulatory loop between integrin/FAK and tumor suppressor p53, and integrin-dependent signaling pathways such as PI3K/Akt/mTOR, NF-κB, and MEK/ERK.…”
Section: Discussionmentioning
confidence: 99%
“…Together, this strongly suggests that Epac-Rap1-mediated survival signals are mediated by integrin-binding to RGD-containing ligands resulting in acquired triapine resistance. In line with this observation, several studies reported a role of altered integrin expression and especially subunit β1 in resistance against diverse cancer therapeutics in solid tumors [34]. For example, temozolomide resistance in glioblastoma [63] and vemurafenib resistance in melanoma are mediated via α5β1 integrin-dimer [64], while doxorubicin resistance in leukemia seems to be promoted by α2β1 [65].…”
Section: Discussionmentioning
confidence: 92%
“…and ultimately leads to cell apoptosis. [47] Thus, the understanding of CAM-DR mechanisms and elucidation the roles of FN1 and integrins such as ITGA1, ITGA5, and ITGA6 may offer valuable therapeutic approaches for drug-resistant ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%